Pentingnya Pendidikan Karakter Dalam Dunia Pendidikan - Mardiah Astuti; Herlina Herlina; Ibrahim Ibrahim; Hellen Prasilia; Dela Sintia; Tri Wulandari (Universitas Katolik Widya Karya Malang, 2023)
This article will discuss the importance of character education in the world of education. Character education is an important part of the life process of students at school, of course it needs comprehensive activities in the process. Character education includes everything about the values ​​of positive people's behavior, helping people to become better people, especially individual students who will shape the next generation of the nation. The role of character education has a major influence on a person's moral development through letter education which will be used as a printer to renew the morals of the Indonesian nation through education. Family, teachers, parents and the environment all influence the cultivation of character education by students.